Assessment of rare earth and actinides (U and Th) elements in soil samples from Kapar industrial area, Selangor. Issue 1 (1st February 2022) - Elias, M S; Azman, M A; Daung, J A D; Hashim, A; Laili, Z; Omar, S A; Shukor, S
Abstract: The study of rare earth and actinide elements have received attention nowadays due to rapid development in the extraction of the rare earth industry in Malaysia. Soil samples (18 areas) collected from the Kapar industrial area were analysed by using the neutron activation analysis (NAA) technique for the determination of rare earth elements and actinides (U, Th) concentration. The concentration of rare earth element such as La, Ce, Nd, Sm, Eu, Tb, Dy, Yb and Lu were ranged from 14.7-61.4, 30.6-132.8, 11.7-44.0, 2.12-9.60, 0.37-1.43, 0.03-1.57, 2.20-7.45, 0.28-0.81, and 1.99-4.15 mg/kg, respectively. The concentrations of uranium and thorium were a range of < 0.1-6.74 and 12.6-30.1 mg/kg, respectively. The results of geo-accumulation indicate the all-rare earth elements can be categorised as uncontaminated in all areas with an Igeo value below 0. The concentration of U can be categorised as uncontaminated to moderately contaminated (Igeo class 1) with Igeo values of 0 to 1 in the area of D, F, H, I, L, and N, whilst other areas can be categorised as uncontaminated with Igeo value < 0 (Igeo class 0). The thorium concentration in B, L, and N areas can be categorised as moderately contaminated with Igeo value 1 to 2 (Igeo class 2), whilst most of the area can be categorised as uncontaminated to moderately contaminated (Igeo values 0 to 1). The sources of Th contamination most likely originated from the anthropogenic and geogenic processes.